Evolving paradigms in the treatment of opioid-induced bowel dysfunction - Jakob Lykke Poulsen; Christina Brock; Anne Estrup Olesen; Matias Nilsson; Asbjørn Mohr Drewes (Therapeutic Advances in Gastroenterology, 2015)
In recent years prescription of opioids has increased significantly. Although effective in pain management, bothersome gastrointestinal adverse effects are experienced by a substantial proportion of opioid-treated patients. This can lead to difficulties with therapy and subsequently inadequate pain relief. Collectively referred to as opioid-induced bowel dysfunction, these adverse effects are the result of binding of exogenous opioids to opioid receptors in the gastrointestinal tract. This leads to disturbance of three important gastrointestinal functions: motility, coordination of sphincter function and secretion. In the clinic this manifests in a wide range of symptoms such as reflux, bloating, abdominal cramping, hard, dry stools, and incomplete evacuation, although the most known adverse effect is opioid-induced constipation. Traditional treatment with laxatives is often insufficient, but in recent years a number of novel pharmacological approaches have been introduced. In this review the pathophysiology, symptomatology and prevalence of opioid-induced bowel dysfunction is presented along with the benefits and caveats of a suggested consensus definition for opioid-induced constipation. Finally, traditional treatment is appraised and compared with the latest pharmacological developments. In conclusion, opioid antagonists restricted to the periphery show promising results, but use of different definitions and outcome measures complicate comparison. However, an international working group has recently suggested a consensus definition for opioid-induced constipation and relevant outcome measures have also been proposed. If investigators within this field adapt the suggested consensus and include symptoms related to dysfunction of the upper gut, it will ease comparison and be a step forward in future research.